The Kirkendall effect-induced formation of FeP@C composites comprising interconnected carbon-coated hollow FeP sub-nanoparticles for efficient alkaline metal storage. Issue 34 (18th August 2021) - Guo, Liping; Qin, Yanmin; Jiang, Zhongqing; Jiang, Zhong-Jie
Abstract : Spindle-like FeP@C with a hierarchical structure comprising carbon-coated hollow FeP sub-nanoparticles and prepared via a Kirkendall-effect-based method exhibits enhanced performance for alkaline metal (K, Na, and Li) storage. Abstract : Structural features are important factors determining the performance of electrode materials for alkaline metal (Li, Na, and K) storage. In this work, we report a fascinating Kirkendall-effect-based method for the synthesis of a spindle-like FeP@C composite with a hierarchical structure comprising carbon-coated hollow FeP sub-nanoparticles (S-HFeP@C). In such a unique structure, the interconnected carbon network and intimate C/FeP contact allow for the ready transfer of charge during redox reactions. The hollow structure of the FeP nanoparticles and their thin walls allow for easy ion diffusion and satisfactory alleviation of the overall strain of FeP, endowing S-HFeP@C with fast reaction kinetics, satisfactory utilization of active material, and excellent structural robustness upon redox reaction. Enhanced performance was observed for Li, Na, and K storage by S-HFeP@C, consisting of a high specific capacity, excellent rate capabilities, and satisfactory cycling stability.